P3-S1.33 Evaluation of the Roche cobas 4800 for the detection of Chlamydia trachomatis and Neisseria gonorrhoeae using minimally invasive samples in women. (10th July 2011) - Hires, L; Van Der Pol, B; Taylor, S; Lillis, R; Body, B
Abstract : Background: The Roche cobas 4800 (cobas) is a new diagnostic assay that utilises an automated workstation to isolate nucleic acids from clinical specimens and a real time instrument for the detection of C trachomatis (CT) and N gonorrhoeae (NG). The objective of this study was to compare the performance characteristics of the cobas to the BD Viper (Viper) and GenProbe Aptima Combo 2 (AC2) assays for the detection of CT and NG using a patient infected standard (PIS). Methods: Specimens were obtained from women attending STD, family planning, or OB/GYN clinics from 12 geographically distinct locations. Urine and vaginal swabs were obtained from each participant as were endocervical (data not shown) and liquid based cytology samples (data not shown). Women were randomised to either self-obtained (SOV) or clinician-obtained (COV) vaginal swab collection. Four sites performed testing by AC2, cobas, and Viper for urine and by cobas for vaginal swabs. A patient was considered infected if at least two of the assays with different molecular targets gave positive results from cervical or urine samples. Results: Overall CT sensitivity ranged from 91.9% to 93.9% and specificity ranged from 99.7% to 99.8% for all sample types. Overall GC sensitivity ranged from 97.0% to 100% and specificity from 99.9% to 100% see Abstract P3-S1.33 table 1 . Conclusions: The cobas assay has excellent sensitivity and specificity when compared to PIS. There was no difference in performance between the SOV and COV specimens or between the vaginal and urine specimens. Self-obtained vaginal swabs provide opportunities for increased efficiency within the clinical settings. The assay is easy to perform, automated, and can be completed in <4 h.